A numerical analysis of the resistance and stiffness of the timber and concrete composite beam = Analiza numeryczna nośności i sztywności belki zespolonej drewniano - betonowej - Szumigała, Ewa; Szumigała, Maciej; Polus, Łukasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents the results of a numerical analysis of the load capacity and stiffness of the composite timber and concrete beam. Timber and concrete structures are relatively new, they have not been thoroughly tested and they are rarely used because of technological constraints.
Keywords: belka zespolona; konstrukcja drewniano-betonowa; nośność; sztywność; analiza numeryczna; composite beam; timber-concrete structures; resistance; stiffness; numerical analysis